One-year post-operative comparison of visual function and patient satisfaction with trifocal and extended depth of focus intraocular lenses. Issue 5 (September 2022) - Law, Elizabeth M.; Aggarwal, Rajesh K.; Buckhurst, Hetal; Kasaby, Hosam E.; Marsden, Jonathan; Shum, Gary; Buckhust, Phillip J.
Purpose: To evaluate visual performance with trifocal and extended depth of focus IOL at 1 year post-operatively. Setting: BMI Southend Hospital. Design: Cohort study. Methods: An age-matched cohort of forty subjects bilaterally implanted with the AT LISA 839MP trifocal IOL (20 patients, 40 eyes) and the Tecnis Symfony extended depth of focus IOL (20 patients, 40 eyes) were assessed at 3–6 months and 12–18 months post-operatively. Primary outcome measures were distance (6 m), intermediate (70 cm), near visual acuity (40 cm), and analysis of defocus profiles. Secondary outcomes included contrast sensitivity, Radner reading performance, quality of vision and assessment of halos. Results: Distance visual acuity (VA) and defocus areas were similar ( p  = 0.07). No significant difference in intermediate VA was noted but the intermediate area of focus was greater in the EDoF (0.31 ± 0.12 LogMAR*m −1 ) compared to the trifocal (0.22 ± 0.08LogMAR*m −1 ) ( p  = 0.02). However, all near metrics were significantly better in the trifocal group. 80% of trifocal subjects were spectacle independent compared to 50% EDoF subjects. Quality of vision questionnaire found no significant differences between groups, however halo scores were greater at 3–6 months in the trifocal group ( p  < 0.01) but no differences were noted at 12–18 months. Conclusions: Near vision is significantly better for the trifocal, thus greater levels of spectacle independence. The range of intermediate vision was greater for the EDoF but no difference in intermediate VA. In the early period, differences in contrast sensitivity and halo size/intensity were noted, however, by one-year these measures were not significantly different.